Anti-SARS-CoV-2 Revaccination Success in Kidney Transplant Recipients With No Initial Humoral Response Is Linked to Primary Vaccine Type - Stumpf, Julian; Schwöbel, Jörg; Karger, Claudia; Schirutschke, Holger; Mauer, René; Klimova, Anna; Tonn, Torsten; Hugo, Christian (Frontiers in Medicine, 2022)
Background While anti-SARS-CoV-2 vaccination success in kidney transplant recipients (KTR) after two doses and 1273-mRNA was associated with higher seroconversion rates compared to BNT162b2-mRNA in our “DIA-Vacc Study” (NCT04799808), it remains unclear whether this may also be the case in non-responding KTR after a third vaccination dose. Materials and Methods Non-responding KTR (after two mRNA vaccinations) were investigated 4.5–6 months after study enrollment at first vaccination. One hundred sixty-six of 193 received a third vaccination between 3.5 and 5 months after the initial study enrollment and were always investigated 4 weeks later, exploring humoral immune response (ELISA) and specific cellular responses (interferon-γ release assay). Sixty-seven of 193 measurements in KTR were done immediately before the third vaccination or in KTR without further vaccination at 4.5–6 months. Results Of 193 KTR with no initial immune response 4 weeks after the second vaccination, 106/87 were immunized twice with 1273-mRNA/BNT162b2-mRNA, respectively. Additional mRNA booster vaccination led to positive seroconversion rates of 30–50%, while 16% of the initial non-responders demonstrated a delayed seroconversion without any booster vaccination. Using logistic regression analysis, a positive IgG response after the third vaccination was 23% more likely if the primary vaccine type was 1273-mRNA compared to BNT162b2-mRNA (OR = 4.420, 95% CI [1.208–16.173], p = 0.025). Primary vaccine type, a weak anti-SpikeS1 IgG response 4 weeks after second vaccination (3.2–35.2 BAU/ml, p < 0.001) and a lack of MMF/MPA as part of the immunosuppressive treatment (trend, p = 0.06) but no other variables studied correlated with seroconversion success. Conclusion This observational study adds important evidence toward using 1273-mRNA as the primary mRNA vaccine type for immunosuppressed KTR.